Traditional fisheries enforcement program: A case of three coastal villages in the eastern part of Oman. (April 2017) - Bose, Shekar; Al-Masroori, Hussein Samh; Al-Habsi, Al-Mutasim Hammoud Ahmed
Abstract: This case study presented perceived views of surveyed fishers and enforcement officials on the efficacy of the existing enforcement programs of the artisanal fisheries sector of Oman. The criteria for evaluating enforcement efficacy were derived from the classical economic view of regulatory enforcement that emphasizes deterrence through legal sanctions - the actual practice in the fisheries sector of Oman. The consistency (or otherwise) in views expressed by both groups was identified using descriptive statistical measures. While some results were promising, the overall results did not provide strong support in rating the efficacy of the existing enforcement practices. An important caveat may apply to this conclusion due to the small number of respondents - fishers in particular - that may restrict the scientific generalization of the results. Nevertheless, the conclusion drawn from the findings may indeed be credible to an extent as it was based on the perceived views of all local enforcement officials, and more interestingly in most cases the perceived views were found to be similar to fishers. Given the existing operational challenges in relation to human and institutional capacity, and the inadequacy of financial and logistical resources, a hybrid approach to fisheries enforcement program was recommended and suggested for its evaluation. The management authority can move forward in this knowledge-building research of portraying enforcement reality through the replication of this study which may also help ensure validity of the results and thus make unbiased strategic decisions on fisheries law enforcement.